Potential use of phytochemical from ethanolic extract of green seaweed Ulva reticulata in aquaculture - NURBETY TARIGAN; AGUS O. SUDRAJAT; HARTON ARFAH; ALIMUDDIN ALIMUDDIN; DINAMELLA WAHJUNINGRUM (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Tarigan N, Sudrajat AO, Arfah H, Alimuddin A, Wahjuningrum D. 2023. Potential use of phytochemical from ethanolic extract of green seaweed Ulva reticulata in aquaculture. Biodiversitas 24: 6868-6879. Ulva reticulata is green seaweed with potential phytochemical properties in the aquaculture sector. Therefore, this study aims to determine phytochemical components and evaluate the toxicity of Ulva reticulata ethanolic extract on aquatic animals. The primary constituents in the sample were extracted using the maceration method with 96% ethanol. The antioxidant activity was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method, while toxicity level was determined using the Brine Shrimp Lethal Test (BSLT) method at concentrations of 0, 10, 100, 300, 500, 1000, and 2000 mg L-1. The results showed that Ulva reticulata ethanolic extract was qualitatively composed of alkaloids, flavonoids, saponins, tannins, phenols, and steroids with mid (++), low (+), low (+), low (+), low (+), and mid (++) activity levels, respectively. Based on quantitative analysis, the sample was composed of sitosterol (19.01 mg g-1), stigmasterol (35.00 mg g-1), saponins (17.04 mg g-1), flavonoids (82.16 mg QE 100 g-1), total phenols (144.00 g QE 100 g-1), and tannins (49.03 mg g-1). Furthermore, Ulva reticulata ethanolic extract had a strong antioxidant level with a 50% inhibitory concentration (IC50) of 53.00 ppm. The toxicity test showed that the 50% lethal concentration (LC50) of the sample was 481.86 mg L-1. These results showed that Ulva reticulata ethanolic extract was a non-toxic material with a high potential for phytochemical properties that could be beneficial for fish growth, reproduction, and health.